A importância da divulgação científica em processos formativos de professores no ensino tecnológico - Andrade, Tatiane Sabino da Silva de (2016)
Research in the scope of the Post-Graduate Program in Technological Teaching, at the Federal Institute of Education, Science and Technology, which discusses the importance of Scientific Divulgation for Teacher Training Processes, taking as a guiding reference the contributions of authors whose ideas harmonize with Proposal of this research, being: the advisor, the studied researchers, added to the answers of the participants in the data collection. The general objective is to: Understand what teachers in continuing education think about the importance of Scientific Dissemination in Teacher Training Processes, to elaborate a process / product, this being an event whose focus is the Scientific Divulgação for the formation Of teachers. Four specific objectives were structured to support the General Objective, namely: a) To discuss approaches related to Teacher Training Processes; B) To establish relationships between Scientific Dissemination and Scientific Communication, considering their differences and contributions to the Dissemination of Processes and Products for Teacher Education; C) Identify what the training teachers think about the scientific dissemination? D) Propose an event for Teacher Training with emphasis on Scientific Dissemination of Processes and Products of Educational Research. The locus of the research was the Federal Institute of Education, Science and Technology of Amazonas (IFAM), Campus Centro (CMC), more specifically the Professional Masters in Technological Teaching and the collaborating subjects for data collection, are teachers in training, enrolled In the 2015 class. The present research is exploratory, with a quantitative approach and we chose as technique for the data collection the questionnaire, with the transformation of the answers into statistics. The choice of the product of this research envisages a formative proposal on Scientific Divulgation for teachers, which integrates a Scientific Broadcasting event.